Copper catalyzed one-pot synthesis of β-ketophosphine oxides from ketones and H-phosphine oxides. Issue 25 (21st June 2017) - Zhang, Zhi-Jie; Yi, Dong; Fu, Qiang; Liang, Wu; Chen, Su-Yuan; Yang, Lu; Du, Feng-Tian; Ji, Jian-Xin; Wei, Wei
Graphical abstract: A simple and efficient copper-catalyzed method has been developed for the synthesis of β-ketophosphine oxides from ketones and H-phosphine oxides in one-pot procedure at room temperature. Highlights: One-pot synthesis of β-ketophosphine oxides from ketones and H-phosphine oxides. The present oxyphosphorylation reaction can be performed under air at room temperature. The carbonyl oxygen atom of β-ketophosphine oxides originated from dioxygen. A radical process is proposed. Abstract: A facile and efficient copper catalyzed one-pot method has been developed for the formation of β-ketophosphine oxides from ketones and H-phosphine oxides under air at room temperature, in which vinylhydrazinedicarboxylate was formed as the key intermediate. Preliminary mechanistic studies indicated that the reaction might involve a radical process and carbonyl oxygen atom of β-ketophosphine oxides came from molecular oxygen.